Ответы и объяснения

2012-11-16T01:25:11+04:00

\left \{ {{x+y+(x+y)^1^/^2=20} \atop {x^2+y^2=136}} \right<=>

 

\left \{ {{x+y+\sqrt{(x+y)}=20} \atop {x^2+y^2=136}} \right \ <=>


Предлагаю заменить \sqrt{(x+y)}=p>0

Тогда:p^2+p=20; \ \ \ p^2+p-20=0; \ \ \ (p+5)(p-4)=0

Получаем

p=- 5;  p=4.

р>0 => p=4

 

Перейдем к начальной системе:\left \{ {{\sqrt{(x+y)}=4} \atop {x^2+y^2=136}} \right\ \ \ <=> \left \{ {{x+y}=16} \atop {x^2+y^2=136}} \right<=>

 \left \{ {{x}=16-y} \atop {(16-y)^2+y^2=136}} \right

 

Решим второе уравнение системы:

16^2+y^2-32y+y^2=136

256+2y^2-32y-136=0

y^2-16y+60=0

(y-10)(y-6)=0 - по Т.Виета

y=10;\ \ \ \y=6

Отсюда, подставляя получаем:

 \left \{ {{x}=16-y} \atop {y=10}} \right\ \ <=>\left \{ {{x}=6} \atop {(y=10}} \right

 \left \{ {{x}=16-y} \atop {y=6}} \right\ \ <=>\left \{ {{x}=10} \atop {(y=6}} \right

  ОТВЕТ: (6;10); (10; 6)